2021
DOI: 10.2478/johr-2021-0005
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Microbiologically Enriched Mineral Fertilizers on Selected Groups of Microorganisms in the Rhizosphere of Strawberry Plants

Abstract: In recent years, the use of bio-fertilizers enriched with specially selected microorganisms has been used more and more often. The beneficial effects of bio-fertilizers enriched with consortia of microorganisms on strawberry plants have been reported previously. The purpose of the research was to determine the effect of bio-fertilizers containing selected fungal and bacterial strains on the microorganisms living in the rhizosphere of strawberry plants. In the experiments described in this paper, synthetic mine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…One of the methods of reducing the amount of fertilizers used to fertilize the soil is to increase their effectiveness by making use of beneficial microorganisms, such as filamentous fungi, arbuscular mycorrhizal fungi (AMF), and also bacteria, which are responsible for improving the growth and physiological condition of plants. These microorganisms are also recommended for the protection of plants against diseases and pests (Sas-Paszt et al 2019a, b, 2020aCanassa et al 2020;Karnwal, Kapoor 2021). There is a belief among producers of agricultural crops that the use of high doses of mineral fertilizers not only harms the environment, but also unnecessarily increases plant production costs and causes eutrophication of surface and ground waters, degradation and pollution of the soil environment, drinking water and air (Boy, Arcand 2013).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…One of the methods of reducing the amount of fertilizers used to fertilize the soil is to increase their effectiveness by making use of beneficial microorganisms, such as filamentous fungi, arbuscular mycorrhizal fungi (AMF), and also bacteria, which are responsible for improving the growth and physiological condition of plants. These microorganisms are also recommended for the protection of plants against diseases and pests (Sas-Paszt et al 2019a, b, 2020aCanassa et al 2020;Karnwal, Kapoor 2021). There is a belief among producers of agricultural crops that the use of high doses of mineral fertilizers not only harms the environment, but also unnecessarily increases plant production costs and causes eutrophication of surface and ground waters, degradation and pollution of the soil environment, drinking water and air (Boy, Arcand 2013).…”
mentioning
confidence: 99%
“…There is a belief among producers of agricultural crops that the use of high doses of mineral fertilizers not only harms the environment, but also unnecessarily increases plant production costs and causes eutrophication of surface and ground waters, degradation and pollution of the soil environment, drinking water and air (Boy, Arcand 2013). An alternative to this is the implementation of modern plant cultivation technologies based on natural raw materials for the production of bio-fertilizers and soil improvers (Sas-Paszt, Głuszek 2019; Grzyb et al 2012a,b;Malusa et al 2013;Derkowska et al 2015;Sas-Paszt et al 2019a, b). The results of many studies from recent years indicate that the use of fertilizers enriched with beneficial strains of bacteria and fungi increases the effectiveness of fertilizers used in plant cultivation (Derkowska et al 2015;Sas-Paszt et al 2019a, b;Delaporte-Quintana et al 2020;Sas-Paszt et al 2020a, b).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Results of numerous experiments have revealed that biofertilizers enriched with arbuscular mycorrhizal fungi and filamentous fungi produce stimulating effects on the growth and reproduction of various plant species (Santhos et al 2018;Sas Paszt et al 2019). Beneficial microorganisms assist the roots in absorbing minerals from the soil and strengthen plant physiology (Mahdi et al 2010;Garima 2019).…”
mentioning
confidence: 99%